Performance-based certification how to design a valid, defensible, cost-effective program - Hale, Judith A.; ProQuest (Firm) (San Francisco : Pfeiffer, 2012)
"Are your employees qualified? Looking for qualified people to do competent work? How do you ensure that the people you hire can do the job right? An ever-increasing number of organizations are asking the same questions. Certification planning is the answer and Performance-Based Certification is the key. This is the only book on the market that addresses the growing need to monitor the qualifications of employees. You'll be able to quickly customize the certification tests and other job aids provided on the accompanying disk. Create a certification program within your organization to: Instill confidence that employees, members, or suppliers are qualified to meet the needs of your customers Ensure that your workforce is trained and competent to their job Make your hiring process more cost effective and legally defendable Recognize competence and consistency of your employees Once you've identified the need for a certification program, what's the next step? All of the answers are here!"--
Includes index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Occupations -- Certification; Professions -- Certification; Electronic books